Mise en œuvre du système multilatéral d’accès et de partage des avantages du Traité international au Rwanda: Analyse contextuelle, recommandations et projet d’acte législatif pour examen - Turamwishimiye, M.R.; Gapusi, J.R. (Bioversity International, 2018)
The study analyzes options for implementing the Plant Treaty's multilateral system of access and benefit-sharing in Rwanda. The study includes an overview of a range of pre-existing Rwandan national policies and laws that are of potential relevance when developing a strategy for implementing the multilateral system, identifying complementarities and (in a few rare cases) conflicts between those policies and laws and Rwanda's commitments under the Plant Treaty. The study presents the results of the authors' analysis of 8 issues that policy makers need to take into consideration when developing a strategy to implement the multilateral system. The study culminates with draft text of a national law to implement the multilateral system in Rwanda, (in a way that is mutually supportive of strategies to implement the Nagoya Protocol). To conduct the study, the authors 'piloted' use of the recently published Decision-making tool for national implementation of the Plant Treaty's multilateral system of access and benefit-sharing (Joint Capacity Building Programme 2018). Click here to access to the English version: https://hdl.handle.net/10568/101203